Effect of Understanding Product Services Shariah Banking Interest of Traders in Submitting Loan: Case Study in Pasar Anyar, Serang, Banten - Ersi Sisdianto; Harrys Pratama Teguh (AL-FALAH : Journal of Islamic Economics, 2020)
Purpose: This study aims to determine the extent of understanding the influence of Sharia banking services products to the merchant interest in applying for loans, another goal was to determine whether the higher level of understanding, the higher the rate of interest applied for a loan. In fact in the district Newer no Sharia Banking Firm and Rural Sharia. There are only 2 Baitul Mal wa Tamwil, it was his existence can not meet the needs of traders to obtain loans in opening a business. Design/Method/Approach : The method used is descriptive analysis method is intended to illustrate how the influence of product understanding Sharia banking services to the merchant interest in applying for loans. The data provided will be processed using chi square and contingency coefficient. The data used consist of interest and the dependent variable is the independent variable is the understanding of the product. The study of the respondents have an understanding of Sharia Banking sufficient to Sharia banking products with 20% and 10% who do not understand. Respondents have sufficient interest to apply for a loan on Sharia banking is 10% interest and 10% had no interestFindings: The influence of the understanding of product and services of Islamic banking on the interest market traders Anyar in applying for loans indicate their relationship fairly closely between two variables, no interest and did not understand at 10%, interest but not understood by 20%, no interest but understood by 20% and interest and understanding by 60%. Sampling technique used is by means of questionnaires and interviews.Originality/Values: The main contribution of this study concern on determine extent of understanding the influence of Sharia banking services products to the merchant interest in applying for loans